Evaluation of Gastroesophageal Reflux Disease in Children on the Autism Spectrum: A Study Evaluating the Tolerance and Utility of the BRAVO Wireless pH Monitoring. Issue 4 (13th July 2022) - Rodriguez, Leonel; Morley-Fletcher, Alessio; Winter, Harland; Timothy, Buie
Abstract : Objectives: Children on the autism spectrum disorder (ASD) may express pain or discomfort through stereotypic or self-injurious behaviors. Gastroesophageal reflux disease (GERD) may be challenging to diagnose in a child who is non-verbal or has impaired communication skills, diagnostic testing for GERD may be the only way to establish the diagnosis. We report our experience using the BRAVO wireless pH monitoring device for the evaluation of GERD in this patient population. Methods: Tolerance and feasibility as well as pH parameters and symptom correlation of the BRAVO pH were evaluated retrospectively in ASD children and compared it to a large cohort of non-ASD children. Only patients with studies lasting >24 hours were included. Results: A total of 172 patients were included, 27 of those were diagnosed with autism (median age 11 years, 17 male). We found no difference in age and weight between both groups but there was a male predominance in the autism group ( P = 0.007). We found no difference in the ability to complete at least 24 hours of study duration between both groups (24/27 or 89% in ASD vs 133/145 or 92% non-ASD patients, P = 0.632). We also found no difference in the median reflux index on the worst day ( P = 0.27) or the average of both days ( P = 0.75), BRAVO pH parameters and the proportion of abnormal studies between ASD and non-ASD children. When evaluating the overall symptom correlation with GER episodes, we did not find a difference between both groups, but we did find a higher symptom correlation for GER symptom during supine position in ASD children. Study was performed for behavioral indication in 11 ASD children, all had normal esophageal mucosa but 4 of those had an abnormal BRAVO pH study. No significant side effects were reported during the study, only 2 patients (1 non-ASD and 1 ASD) complained of self-limited chest pain. Conclusions: BRAVO wireless pH is well tolerated and feasible in evaluating GER and behavioral symptoms in ASD children and provides a reasonable alternative to standard trans-nasal pH monitoring.